ANALISIS PERAN GURU DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA DI SDN SERPONG 2 TANGSEL - Rahmat Rahmat; Amaliyah Amaliyah; Nining Wulandari; Muhamad Arya Dika (STKIP Pesisir Selatan, 2026)
Learning motivation plays a crucial role in determining students’ level of participation and academic success, particularly at the elementary school level. Teachers hold a strategic position in fostering and enhancing students’ motivation through the implementation of effective instructional strategies. This study aims to examine the role of teachers in improving students’ learning motivation at SDN Serpong 2 Tangerang Selatan. The research employed a qualitative approach using a case study design. Data were collected through observation, interviews, and documentation, involving elementary school teachers and students as research participants. The collected data were analyzed using qualitative data analysis procedures, including data reduction, data presentation, and conclusion drawing. The findings reveal that teachers act as motivators by applying various strategies, such as assigning challenging tasks aligned with students’ abilities, providing encouragement and positive reinforcement, creating a supportive and conducive classroom environment, and offering individual guidance to students who experience learning difficulties. These strategies contribute to increasing students’ interest, enthusiasm, and active involvement in the learning process. Nevertheless, teachers encounter several challenges, including limited instructional time, differences in students’ characteristics and abilities, and the underutilization of innovative learning media.